Tinjauan Poster Pencegahan Virus Corona-19 Guna Meningkatkan Kesadaran Masyarakat Terhadap Pandemi Global - Galih Putra Pamungkas; Arsita Pinandita (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2021)
Indonesia started the war to deal with the Corona Virus pandemic (Covid 19 Virus) which has begun to enter its territory. A survey conducted by Facebook shows that with the entry of the Corona Virus (Covid 19 Virus) in Indonesia, almost 80% of respondents from Indonesia are afraid of contracting the Corona Virus (Covid 19 Virus), of course this is based on the absence of a vaccine to overcome the Corona Virus ( Covid 19) worldwide. In addition, there is concern that this virus will have a negative impact on various sectors, especially the economic sector. Various ways and movements to fight the virus and give positive spirit were carried out by the community. One of them is through posters. But unfortunately, there are also many posters that contain hoax information, this has resulted in public distrust of the information in the postersDeparting from the above, the authors intend to design an educational poster for the prevention of the Corona-19 virus as an effort to increase the awareness of the Indonesian people towards the global pandemic. This poster will become a national movement with credibility that can be justified.